PENINGKATAN KEMAMPUAN MENULIS DENGAN MODEL PEMBELAJARAN ADVANCE ORGANIZER PADA SISWA SMAN 7 MATARAM - Farida Fitriani (Jurnal Paedagogy, 2017)
This study aims to obtain objective descriptions of learning with the advance organizer model in class XI students of SMA Negeri 7 Mataram to improve their short story writing skills. This type of research is classroom action research. The implementation consists of two cycles, each cycle consisting of two meetings. The data were collected by using the literature method and the method of observation, while the data were analyzed using the mastery learning formula. Based on the results and discussion, it can be concluded that the ability to write short stories using the advance organizer learning model in class XI students of SMA Negeri 7 Mataram has increased, both in terms of process and results. The process improvement is indicated by almost all indicators of action that have been implemented by all students. While the increase in results can be seen from the average value of each aspect has increased: (1) aspects of the theme, from an average of 79.16 in the first cycle to 87.90 in the second cycle; (2) the opening aspect of the story has increased from the first cycle with an average value of 65.83 to 73.38 in the second cycle; (3) Character aspect, from cycle I 70.83 to 72.58 in cycle II; (4) the background aspect of the average value in the first cycle of 68.33 to 72.58 in the second cycle; (5) plot aspects, from an average value of 69.16 to 78.22 in the second cycle; (6) impression aspect, the average value from 62.5 to 69.35 in cycle II.